2005
DOI: 10.1152/ajplung.00382.2004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of pulmonary manganese absorption: evidence for increased susceptibility to manganese loading in iron-deficient rats

Abstract: of pulmonary manganese absorption: evidence for increased susceptibility to manganese loading in iron-deficient rats. Am J Physiol Lung Cell Mol Physiol 288: L887-L893, 2005. First published December 23, 2004; doi:10.1152/ajplung.00382.2004.-High levels of airborne manganese can be neurotoxic, yet little is known about absorption of this metal via the lungs. Intestinal manganese uptake is upregulated by iron deficiency and is thought to be mediated by divalent metal transporter 1 (DMT1), an iron-regulated fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
1
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 33 publications
2
34
1
1
Order By: Relevance
“…The HFE variant may reduce immediate absorption of toxic divalent metals in particulate matter, because subjects with this variant have higher iron stores and downregulated iron absorption. Recently, Heilig et al 35 demonstrated that iron-deficient rats will absorb increased levels of manganese instilled in the lungs. The present findings are consistent with those results and support the hypothesis that genes that regulate intestinal absorption of divalent metals also regulate pulmonary metal absorption.…”
Section: Discussionmentioning
confidence: 99%
“…The HFE variant may reduce immediate absorption of toxic divalent metals in particulate matter, because subjects with this variant have higher iron stores and downregulated iron absorption. Recently, Heilig et al 35 demonstrated that iron-deficient rats will absorb increased levels of manganese instilled in the lungs. The present findings are consistent with those results and support the hypothesis that genes that regulate intestinal absorption of divalent metals also regulate pulmonary metal absorption.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney studies remain to show the importance of DMT1 as well as different isoforms (Abouhamed et al, 2006;Canonne-Hergaux & Gros, 2002;Wareing et al, 2003;. Pharmacokinetic studies show that iron status can alter lung Mn transport to circulation Heilig et al, 2005;Thompson et al, 2006) DMT1 is not the transporter involved . Recently is has been verified that the b/b Belgrade rat lacks transport mechanisms for divalent metals in its small intestine (Knopfel et al, 2005).…”
Section: Divalent Metal Transporter (Dmt1) In Mn Transportmentioning
confidence: 99%
“…79 Surprisingly, 54 Mn also failed to associate with Tf present in BAL from control rats. 64 This combined evidence completely rules out a role for DMT1, suggesting the existence of additional transport pathways for manganese in the lungs. …”
Section: Pulmonary Manganese Uptake and Iron Deficiencymentioning
confidence: 84%
“…[61][62][63] These channels, and others, are thought to maintain fluid balance in lungs, but potential roles in the transport of manganese and other metals are possible as well. 64 …”
Section: Other Manganese Transporters: Non-selective Ion Channelsmentioning
confidence: 99%
See 1 more Smart Citation